Perceived stress and family adaptability in head and neck cancer patients receiving radiotherapy: the chain-mediated effect of social support and family resilience - Li, Xiaoru; Zhu, Yu; Wan, Hongwei (Frontiers in Psychiatry, 2025)
ObjectivePatients with head and neck tumors undergoing radiotherapy are burdened with a variety of disease-related stressors that may affect their family adaptability. The aim of the present study was to investigate the relationship between perceived stress and family adaptability in patients with head and neck tumors and to analyze whether social support and family resilience play a mediating role in this relationship.MethodsThe convenience sample approach was utilized to recruit 316 patients with head and neck tumors who received radiation. Self-developed general information questionnaires, the Chinese Perceived Stress Scales, Social Support Rating Scale, the Shortened Chinese Version of the Family Resilience Assessment Scale, and Family Adaptability Scale were used to collect data. Bootstrap methods to analyze independent and chained mediation effects between variables.ResultsThe research participants had a mean age of 43.63 ± 12.78 years, were mostly male (61.7%), married (85.8%), had a university education (51.6%), were uninsured (50.9%), had ear, nose, and throat tumors (56.3%), and had an illness duration of 1-6 months (43.4%). The findings of the chain mediation effect research indicate that the direct negative effect of perceived stress on family adaptability (-0.163) accounted for 45.63% of the overall effect (-0.355), while the indirect effect (-0.194) accounted for 54.37%. Perceived stress independently mediated family adaptability through social support (effect: -0.062) and family resilience (effect: -0.080), with the independent mediator effect accounting for 32.12% and 41.45% of the indirect effect, respectively, and chain-mediated mediation of social support and family resilience, with the chain effect (-0.051) accounting for 31.30%.ConclusionPerceived stress in patients with head and neck cancer receiving radiotherapy directly or indirectly negatively affects family adaptability. Clinical staff should meet the patient’s health care service needs while also utilizing the family’s internal and external resources to reduce disease-related stress and improve family adaptability.